An Implementation of Restorative Justice in Settlement Framework Criminal Acts Fraud and Employment to Provide Useful And Fair Legal Guarantee (Study In Police Regional North Sumatra) - Mangara Hutagalung; Ismaidar; T Riza Zarzani (IHSA Institute, 2022)
The settlement of criminal cases of fraud and embezzlement is generally the application of compensation by the perpetrator and his family to the victim or his family to avoid the consequences of revenge. The main principle of Restorative Justice is the participation of victims and perpetrators, the participation of citizens as facilitators in resolving cases so that there is a guarantee that the child or perpetrator will no longer disturb the harmony created among the community. This research is aimed at legal arrangements for fraud and embezzlement through restorative justice efforts, to analyze the application of restorative justice in the settlement of fraud and embezzlement crimes and forms of legal remedies provided by the police in resolving criminal acts of fraud and embezzlement through restorative justice in this study at regional Police of North Sumatra which is related to the problem of this thesis. This research uses research specifications, namely analytical descriptions that describe or describe events as stated by the respondent in writing or verbally, as well as actual behavior, which is researched or studied in its entirety. In the application of restorative justice and penal mediation, restorative justice is a concept of thought that responds to the development of the Criminal Justice System by focusing on the need for community involvement and victims who feel left out by the mechanisms that work in the current SPP. Police efforts by taking preventive and repressive actions in dealing with embezzlement and fraud.